When sounds, colors, and shapes meet: Investigating children's audiovisual art in response to classical music. (November 2019) - Elkoshi, Rivka
This study was designed to investigate children's audiovisual art, following intuitive listening to complete classical works from different historical periods. The study aimed to examine the effect of different musical stimuli on children's audiovisual output. Two related questions were asked: (1) How do children visually and verbally represent music from different historical periods? (2) What musical and extra-musical elements are represented? Participants were 181 second graders (age 7.0–8.5). Three compositions were presented: a 12th-century anonymous choral from the liturgical drama " Danielis Ludus, " Chopin's prelude op. 28 no. 10, and Bartók's " Melody in the Mist " Vol. 4 no. 107, from " Mikrokosmos ." Each composition is based on distinct musical parameters: vocal timbre, melodic contour, and texture alternations, respectively. Data consisted of 495 audio-graphic productions and related accounts. Analysis progressed in three stages abbreviated MSC: Morphological dimensions, focusing on type of symbols employed; Structural dimensions, focusing on the overall graphical design; and Conceptual dimensions focusing on the generic meanings of the productions. Results indicated significant differences in children's reactions to each of the three compositions, showing that MSC dimensions are influenced by the type of music presented and that differences in MSC dimensions are statistically significant. Experiencing "audiovisuology" in school is one way of promoting art integration.